The help relationship in clinical nursing education - Silva, Ernestina (2017)
The clinical nursing education involves considerable effort from students. They established interpersonal relationships and they are active participants in this process. What is the perception of nursing students and the parents of the children in the help relationship (HR) developed during the clinical training were some of our research questions. We aimed to identify factors that influence interpersonal relations between nursing students and the mothers of hospitalized children; analyze the relationship between the perspective of students and the parents of the children on the HR developed during the clinical training; identify feelings experienced by students and parents in the relational process of care taking. As methods quantitative, descriptive and correlational study, conducted in a sample of 139 nursing students and 73 mothers of hospitalized children. It was used a questionnaire, which includes socio-demographic, training and clinical characterization and the BarrettLennard Relationship Inventory (BLRI), which evaluates the help relationship in four dimensions have been used. The dimensions of help relationship - Level of Regard, Empathic Understanding and Unconditionally Respect - are scored positively by students and mothers. The Congruence of performance is evaluated negatively by mothers while students are evaluated positively. Prevailing negative feelings referenced by students and the positive feelings by mothers. The perception of help relationship is influenced by some socio-demographic variables of students and mothers. All dimensions establish a dependent relationship with the group of students and mothers. The perception of students on the HR is positive, the perception of mothers regarding student performance is also positive, except in Congruence.